Not Just Plug and Play: Integrating Professional Skills Development into Undergraduate Experiential Learning Courses - Steven Henle; Susan T. Dinan; Megan Marcoux; Janette Barrington; Julia L. Ginsburg; Sandra Gabriele (Canadian Journal for the Scholarship of Teaching and Learning)
This study evaluated the effectiveness of the FUSION Skill Development Curriculum in maximizing students' self-assessment of professional skills when integrated as a graded component in capstone internship courses. The course instructors were co-investigators in a scholarship of teaching and learning (SoTL) project that used measures embedded in the curriculum to study student learning outcomes. An essential benefit of the curriculum was identified as the potential for life-long learning through metacognition. A data-driven approach to curriculum integration triggered changes in teaching practices associated with motivational design principles. These changes included allocating time for peer discussion of professional skills, scaffolding feedback aligned with internship learning, and taking a holistic view of skill development throughout an academic program. Overall, the study explored the nexus between skill development and internship/experiential learning and generated practical insights for scaling up the FUSION initiative, as well as a proposed model of curriculum renewal for professional skills development.